KONTRUKSI STEREOTIP GENDER DAN IMPLIKASINYA TERHADAP MARGINALISASI PENDIDIKAN PEREMPUAN DI DESA WISATA ADAT SADE - Fiona Helga Milla; Indira Sabila Arsyad; Muh Aditya Bilal; Nurhalifah Nurhalifah; Mila Noviana (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study aims to explore how gender stereotypes toward women are reproduced within the social life of the Sade Traditional Tourism Village, Central Lombok, and to analyze their relationship with the level of formal educational attainment among girls in the community. Sade Village is a Sasak indigenous community that continues to preserve its traditional values, social norms, and customary regulations (awig-awig) as the foundation of everyday life. Despite the growth of tourism, these cultural practices continue to shape gender-based roles and expectations. This research employed a qualitative method using an empirical approach. Data were collected through direct observation, in-depth interviews with ten local informants, including traditional leaders, parents, women weavers, and community members, and supported by documentation as complementary data. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the low level of formal educational attainment among women is strongly influenced by cultural stereotypes that confine women to domestic responsibilities. The obligation for girls to master weaving (nyesek) from an early age is regarded as an indicator of social readiness for marriage, causing formal education to be viewed as a secondary priority. As a consequence, women experience limited access to education, the persistence of gender-based marginalization, and the reproduction of unequal gender roles within the social and economic structure of the local tourism community.